RUPTURE OF THE SPLENIC ARTERY ANEURYSM IN PANCREATIC PSEUDOCYST FOLLOWED BY BREAKTHROUGH INTO THE STOMACH - K. P. Pashkin; E. V. Motyrova; I. A. Lunkov; V. I. Matrosov; D. V. Mishin; A. S. Kuznetsova; A. V. Klimenko; D. A. Bulatov (Вестник хирургии имени И.И. Грекова)
The article presented the clinical case of massive bleeding due to a rupture of the splenic artery aneurysm in a pancreatic pseudocyst followed by breakthrough into the stomach.The authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.